2010
DOI: 10.1097/prs.0b013e3181c2a5cc
|View full text |Cite
|
Sign up to set email alerts
|

Facial Transplantation: An Anatomic and Surgical Analysis of the Periorbital Functional Unit

Abstract: Surgical harvest of a functional periorbital allotransplant is technically feasible. Revascularization of the isolated periorbital unit is influenced by variations in regional anatomy and cannot be guaranteed by a single vascular pedicle. The orbicularis oculi muscle and its innervation can be preserved, and recovery, albeit without the certainty of reflexive blinking, is expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…None of the dissected cadavers had a history of head or neck trauma, facial surgery, facial deformity, or congenital malformation. Periorbital subunit harvest, as previously described, 3 , 6 , 7 , 9 , 10 was based on a bipedicle vascular supply via the facial vessels and superficial temporal vessels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the dissected cadavers had a history of head or neck trauma, facial surgery, facial deformity, or congenital malformation. Periorbital subunit harvest, as previously described, 3 , 6 , 7 , 9 , 10 was based on a bipedicle vascular supply via the facial vessels and superficial temporal vessels.…”
Section: Resultsmentioning
confidence: 99%
“…2 , 3 Consequently, a paradigm shift in the attitudes toward facial VCA 5 has prompted reconstructive surgeons to consider transplanting isolated periorbital tissues. 6 , 7 …”
mentioning
confidence: 99%
“…Overall, given the significant progress that has been made in the last decade toward minimization of long-term immunosuppression and tolerance induction wider application of innovative reconstructive options such as facial unit or nasal transplantation can now be realized for patients not amenable to conventional methods of repair. Indeed, anatomical studies for periorbital, 7,8,30 eyelid, 9 and ear units 31 have been reported, although no clinical cases have been published.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of transplantation of the upper third of the face or for transplantation of a functional subunit eyelid flap, the superficial temporal artery may be able to be used. 32 The venous outflow would be via the corresponding facial, transverse facial, or superficial temporal veins. While a single arterial and venous anastomosis would likely be sufficient, more than one may be done depending on the size of the facial allograft and the observed flow and perfusion via a single set of vessels.…”
Section: Facial Allotransplantationmentioning
confidence: 99%